Editorial Remarks: Conversations with Indigenous Knowledges - Hancock, Robert L. A.; Moran, Ry; Newman, Carey; Walsh, Andrea; Rogers, Shelagh (KULA)

(untitled) (University of Victoria Libraries, 2021)
A brief introduction to “Indigenous Knowledges,” a special issue of KULA: Knowledge Creation, Dissemination, and Preservation Studies that includes sixteen contributions in diverse formats, including multimedia. In these editorial remarks, the editors reflect on the discussions that led to the special issue, their responsibility to honour the work of contributors from many different nations and communities, the ways that conventional forms of academic writing can be inhospitable to Indigenous knowledges, and conversation as methodology. This short introduction also links out to the recording of the virtual launch of “Indigenous Knowledges,” hosted and moderated by Shelagh Rogers and featuring editors Robert L. A. Hancock, Ry Moran, Carey Newman, and Andrea Walsh and contributors Jessie Loyer, Darrell Loyer, and Barry Pottle.